2021
DOI: 10.3390/met11060877
|View full text |Cite
|
Sign up to set email alerts
|

Compression Behaviour of Wire + Arc Additive Manufactured Structures

Abstract: Increasing demand for producing large-scale metal components via additive manufacturing requires relatively high building rate processes, such as wire + arc additive manufacturing (WAAM). For the industrial implementation of this technology, a throughout understanding of material behaviour is needed. In the present work, structures of Ti-6Al-4V, AA2319 and S355JR steel fabricated by means of WAAM were investigated and compared with respect to their mechanical and microstructural properties, in particular under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These barriers relate, to a large extent, to the scarcity of test data on the mechanical properties and structural performance of additively manufactured materials [12,13,14]. In light of this, there has recently been a growing number of research groups investigating the microstructural and mechanical properties of different WAAM materials, including lowalloy steels [15,16,17,18,19] and various stainless steel alloys [20,21,22,23,24,25,26,27]. The aforementioned studies have revealed a degree of anisotropy in the behaviour of WAAM stainless steel material, i.e.…”
Section: Torchmentioning
confidence: 99%
“…These barriers relate, to a large extent, to the scarcity of test data on the mechanical properties and structural performance of additively manufactured materials [12,13,14]. In light of this, there has recently been a growing number of research groups investigating the microstructural and mechanical properties of different WAAM materials, including lowalloy steels [15,16,17,18,19] and various stainless steel alloys [20,21,22,23,24,25,26,27]. The aforementioned studies have revealed a degree of anisotropy in the behaviour of WAAM stainless steel material, i.e.…”
Section: Torchmentioning
confidence: 99%
“…The other results confirm the distribution of the tooth root and the bending tests and thus the determined general manufacturing factors for the additive processes. The material-dependent anisotropic behaviour of the compression specimens manufactured with the WA-DED method described by Abbaszadeh can consequently be confirmed [23]. Furthermore, Longhitano et al determined anisotropic mechanical properties for L-PBF manufactured components [22].…”
Section: Compression Testmentioning
confidence: 87%
“…Abbaszadeh et al analysed the results of the compression behaviour of WA-DED structures for different materials. They showed material-dependent anisotropic behaviour [23]. Bambach et al examined the hot forming behaviour of Ti6Al4V made by AM.…”
Section: Investigation Of the Obtained Mechanical Properties By Destr...mentioning
confidence: 99%
See 1 more Smart Citation